Distinção e o posicionamento no campo da ciência da informação: análise de indicadores métricos de bolsistas produtividade em pesquisa do CNPq - Villanova, Andre Philippe (Universidade Federal de São Carlos, 2020)
All phases of science production go through internal and external evaluation screens, approved by the scientific community itself. The positive result of these evaluations is one of the aspects that defines the positions that the agents involved in scientific work can reach before this scientific community. The objective of this research is to investigate quantitative aspects of the scientific production of Information Science in relation to the Bourdieusian precepts of distinction and positioning in the field. To this end, an academic-scientific field will be taken as an excerpt, namely, the CNPq productivity fellows in this area. To achieve the proposed objective, the theoretical-reflective study was adopted as a methodology, based on the reading and inferences of Bourdieusian concepts and the use of the bibliometric approach. The sources of data collection were the CAPES Portal and the Lattes Platform. The data were processed using Excel tools and Vantage Point software. In general, there is an advantage for granting scholarships to researchers who already had processes contemplated, this fact is associated with the “power” of accumulated capital. It is observed that a researcher who reaches this scholarship tends to seek the permanence of his position of influence in the field, which culminates in a reasonable number of researchers who remain with the funding for more than fifteen or twenty years. There are indications that the number of process concessions is a tool to regulate the number of researchers. Thirty percent of the researchers had mobility from one category to another higher, indicating that there is a need for greater investment of time to ascend in the categories. As for the profile of the fellows, the group is formed by a female majority. There is a balanced proportion of the typology of the scholarship in the genres, this data denotes that there are no signs of the “gender” factor being preponderant for the distinction in the typology of the scholarships. The proportion of foreign researchers is very small in relation to national researchers, which may indicate that this field in Brazil does not present a distinction related to nationality. The two most used forms of scientific communication for fellows are journals and congresses. Most articles are published in national journals. The CBT guidelines are greater than the master's, which in turn are greater than the doctorate, which surpass the postdoc. The narrowing of the guidelines can represent that the higher titles are more scarce, demonstrating that the distinction and positioning that a legitimate title occurs in stops and the dispute becomes more fierce along the way. The indicators analyzed in this research reveal the distinction and positioning of the field of Information Science, but it does not mean that they condition researchers, this dynamic occurs through the structure and behavior of agents in the field, as described by Bourdieu and identified in this research, it is not a question of determinism or subjectivism, but of relations based on the dispute for positions in the scientific field.
Distinction and positioning in the field of information science: analysis of metric indicators of scholarships productivity in CNPq research
Keywords: Bibliometria; Bolsistas Produtividade CNPq; Ciência da informação; Bourdieu; Bibliometry; CNPq Productivity Fellows; Information science; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO